Updated Review of the Acoustic Modulation of Sleep: Current Perspectives and Emerging Concepts - Cordi MJ (Dove Medical Press, 2021)
Maren Jasmin Cordi1,2 1Department of Psychology, Division of Cognitive Biopsychology and Methods, University of Fribourg, Fribourg, Switzerland; 2Centre of Competence Sleep & Health Zurich, University of Zurich, Zurich, SwitzerlandCorrespondence: Maren Jasmin CordiUniversity of Fribourg, Division of Cognitive Biopsychology and Methods, Rue P.A. de Faucigny 2, Fribourg, 1700, SwitzerlandTel +41 26 300 7678Email maren.cordi@unifr.chAbstract: With growing interest in the use of acoustic stimuli in sleep research and acoustic interventions used therapeutically for sleep enhancement, there is a need for an overview of the current lines of research. This paper summarizes the various ways to use acoustic input before sleep or stimulation during sleep. It thereby focuses on the respective methodological requirements, advantages, disadvantages, potentials and difficulties of acoustic sleep modulation. It highlights differences in subjective and objective outcome measures, immediate and whole night effects and short versus long term effects. This recognizes the fact that not all outcome parameters are relevant in every research field. The same applies to conclusions drawn from other outcome dimensions, consideration of mediating factors, levels of stimulation processing and the impact of inter-individual differences. In addition to the deliberate influences of acoustic input on sleep, one paragraph describes adverse environmental acoustic influences. Finally, the possibilities for clinical and basic research-related applications are discussed, and emerging opportunities are presented. This overview is not a systematic review but aims to present the current perspective and hence summarizes the most up-to-date research results and reviews. This is the first review providing a summary of the broad spectrum of possibilities to acoustically influence sleep.Keywords: acoustic stimulation, sleep modulation, sleep disturbance, therapeutic intervention